Harmonizing Regional and National Regulations to Accelerate Stunting Reduction in Gowa Regency - Widyansyah, Aliffiani; Sapsudin, Asep (LifeSciFi, 2026)
Stunting remains a serious public health problem in Indonesia, affecting children’s physical growth, cognitive development, and long-term productivity. The central government issued Presidential Regulation No. 72 of 2021 on the Acceleration of Stunting Reduction, targeting a national prevalence rate of 14% by 2024. However, a gap persists between das sollen (normative regulation) and das sein (implementation reality), where local governments face challenges such as limited budgets, weak cross-sectoral coordination, and suboptimal institutional capacity. Gowa Regency, as one of the priority loci for stunting reduction, is essential to study in the context of synchronization between national and local regulations. The main problem addressed in this study is the suboptimal synchronization between national and local regulations in accelerating stunting reduction in Gowa Regency. This condition leads to inconsistencies between national policy directions and program implementation at the local level, potentially hindering the achievement of national targets. This study aims to assess the alignment between Presidential Regulation No. 72 of 2021 and Gowa Regent Regulation No. 5 of 2023 using a normative juridical method with vertical and horizontal synchronization approaches. The results indicate that the synchronization of regulations in Gowa Regency is high in normative aspects but remains limited in technical implementation. Although stunting prevalence decreased from 33% in 2022 to 17% in 2024, the figure remains above the national target. The study suggests strengthening adaptive synchronization through cross-sectoral data integration, performance-based budgeting, and institutional capacity enhancement to accelerate sustainable stunting reduction.